Report of a new genus Mirigryllus belonging to tribe Modicogryllini, with a new species M. nigrus from Zhejiang, China (Orthoptera: Gryllidae: Gryllinae: Modicogryllini) - He, Zhu-Qing; Shen, Chu-Ze; Wu, Xue; Chen, Lin; Li, Kai (Zootaxa, 2020)
A new genus (Mirigryllus He gen. nov.) with a new species (M. nigrus He sp. nov.) is reported from Zhejiang, China. The morphology and calling songs of the new species are provided. The features that different from tribe Modicogryllini spp. include long and thin posterior epiphallic lobes, ectoparameron transparent. Two genes, COI and 18S, of 11 Modicogryllini species were sequenced, and phylogenetic tree was reconstructed. The results support the validation of the new species. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).